1997
DOI: 10.1111/j.1553-2712.1997.tb03809.x
|View full text |Cite
|
Sign up to set email alerts
|

Use of the Alveolar Dead Space Fraction (Vd/Vt) and Plasma D‐dimers to Exclude Acute Pulmonary Embolism in Ambulatory Patients

Abstract: Objective: To evaluate the utility of a modified calculation of the alveolar dead space fraction (Vd/Vt), combined with plasma D-dimers, to aid in the exclusion of acute pulmonary embolism (PE). Methods: A prospective comparison of screening modalities was performed in a metropolitan teaching ED. Ambulatory patients evaluated for PE underwent simultaneous end-tidal CO, and arterial blood gas determinations, as well as venous latex-agglutination D-dimer quantification. The modified Bohr equation was used to cal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
44
0
10

Year Published

1999
1999
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(55 citation statements)
references
References 35 publications
1
44
0
10
Order By: Relevance
“…11,15,18,[21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] The three most widely used clinical decision rules are the simplified Wells score, the revised Geneva score, and the pulmonary embolism rule-out criteria (PERC) rule. The simplified Wells score comprises seven variables and has been derived and validated in the North American population.…”
Section: Discussionmentioning
confidence: 99%
“…11,15,18,[21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] The three most widely used clinical decision rules are the simplified Wells score, the revised Geneva score, and the pulmonary embolism rule-out criteria (PERC) rule. The simplified Wells score comprises seven variables and has been derived and validated in the North American population.…”
Section: Discussionmentioning
confidence: 99%
“…Despite this positive report, there is a scarcity of data documenting pulmonary gas exchange and/ I or early pulmonary outcomes in this patient population 22 . The rationale for measuring alveolar dead space to demonstrate a functional consequence of pulmonary embolization has been well documented [7][8][9]11,12,14 . In an experimental study involving glass-bead embolization, alveolar dead space increased proportionate to the degree of pulmonary vascular obstruction in mechanically ventilated goats 15 .…”
Section: Risk Of Postoperative Pulmonary Dysfunctionmentioning
confidence: 99%
“…Furthermore, experimental studies on the effect of pulmonary embolism have demonstrated an increase in alveolar dead space secondary to a reduction in perfusion of the affected lung 16 . Measurement of alveolar dead space is a sensitive screening test (sensitivity of 88%) for acute pulmonary emboli in ambulatory patients 12 , and it has a high sensitivity and specificity for detection of pulmonary emboli in mechanically ventilated patients with intrinsic lung disease (asthma, chronic obstructive pulmonary disease, and so on) 9,11 . Thus, there is ample evidence suggesting that pulmonary gas exchangespecifically, alveolar dead space-should change if a large embolic burden is routinely induced by reaming and/or nailing of a fractured femoral shaft.…”
Section: Risk Of Postoperative Pulmonary Dysfunctionmentioning
confidence: 99%
See 2 more Smart Citations